New services development: a study in the context of a health organization. Issue 4 (6th September 2018) - Eberle, Luciene; Milan, Gabriel Sperandio; De Toni, Deonir; Lazzari, Fernanda
Abstract : Purpose: The purpose of this study is to highlight the understanding of the consequent factors of new services development (NSD) in the literature owing to the impact on organizational competitiveness, especially in professional services, such as that investigated by health plan operators in the present study. Design/methodology/approach: The sample (customer of family health plans) consisted of 255 valid cases. For the analysis of the data, multivariate statistical techniques were used through the modeling of structural equations. Findings: The results found evidence of the significant relationships between the NSD considering the constructs, client orientation, reputation, professional competences and customer retention, as consequences of the NSD, which impact on the success of the new services launched by the health plan operator from the perception of the customer. Practical implications: This implies that health plan operators need to develop new customer-oriented services by investing in new technologies and having more trained and qualified staff so that they can deliver superior services and, as a consequence, have a more profitable relationship with customers. Originality/value: The new services may result in greater organizational performance and greater competitiveness for health service providers.